On the effect of anion exchange ionomer binders in bipolar electrode membrane interface water electrolysis. Issue 25 (24th May 2021) - Mayerhöfer, Britta; Ehelebe, Konrad; Speck, Florian D.; Bierling, Markus; Bender, Johannes; Kerres, Jochen A.; Mayrhofer, Karl J. J.; Cherevko, Serhiy; Peach, Retha; Thiele, Simon
Abstract : Bipolar interfaces located directly between a proton conducting membrane and an anion exchange ionomer based anode catalyst layer are investigated in membrane electrode assemblies for water electrolysis. Abstract : Bipolar membrane|electrode interface water electrolyzers (BPEMWE) were found to outperform a proton exchange membrane (PEM) water electrolyzer reference in a similar membrane electrode assembly (MEA) design based on individual porous transport electrodes (PTE) and a free-standing membrane. We present a detailed study on bipolar interfaces between anion exchange ionomer (AEI) based anode catalyst layers in direct contact with a PEM aiming to unravel influences of local pH, the water splitting bipolar interface and catalyst layer structure. It is conventionally accepted that AEIs used in anion exchange- and bipolar membrane water electrolysis conduct hydroxide anions and ensure a high pH environment in the catalyst layer. We have investigated the effect of different ionomers on the local pH at a metal surface and found a strong correlation with the pH of the surrounding solution rather than the ionomer type. Thus, solely the use of an AEI cannot maintain high pH. A study on BPEMWEs revealed strong indications for the co-existence of a water dissociating bipolar interface, and an acidic oxygen evolution mechanism. The superior performance compared to a PTE-based PEM water electrolyzer seems to stem from reduced contact resistances due to adhesive effects between the oppositely charged polymers. Our study shows that the bipolar approach can be utilized to make PTE-based electrolyzers competitive to commonly employed catalyst coated membranes.